Determinants of Smartphone Addiction and its Influence on Students’ Academic Performance - Sana Mairaj Bugti; Firdous Bugti; Pir Suhail Ahmed Sarhandi (PJDOL, 2023)
Smartphone is the mostwanted gadget of this era and smartphone addiction is the association with its use. This research aims to find the role of craving, social relationships, and overuse of smartphone as determinants of smartphone addiction and its influence on students’ academic performance. This study uses purposive sampling (non-probability) technique and survey method was adopted. The data was collected through online questionnaire via Google Forms from 300 students of Bachelor of Education (hons.) studying in the Department of Teacher Education, Shah Abdul Latif University, Khairpur Mirs’. For hypotheses testing, structural equation modeling was used. The findings indicated that social relationships and overusage of smartphone were positively affecting smartphone addictionwhereas craving to use smartphone was proved insignificant in creating smartphone addiction, further it was found that the created smartphone addiction among students was positively and significantly affecting their academic performance. This study recommends that use of smartphone must be encouraged in teaching learning for students’ effective academic performance.